A Literature Review of Knowledge Management Role in Employee Performance - Sulistyanto, Tri Hadi; Djamil, Masyhudzulhak; Sutawidjaya, Ahmad Hidayat; Nawangsari, Lenny Christina (JDM (Jurnal Dinamika Manajemen), 2021)
This review aimed to discuss current literatures of Knowledge Management (KM) role in employee performance. This paper reviewed articles about the effect of KM on performance from several dif- ferent countries. The result of the study shows that all article reviewed have the same same conclusion that there is a positive relationship between KM and employee performance. The important findings suggest that KM is a major indirect factor of organizational performance. Also, KM occupies an impor- tant role in forming an effective platform for learning organizations. However, how knowledge man- agement influences competitive advantage such as knowledge, behavior, attitude, and its influence on performance had not attract the attention of researchers. This study suggests future studies to include intervening variables such as competitive advantage, knowledge, behavior, and attitude, to gain a deeper understanding of knowledge management’s role in improving employee performance..